Feasibility and Safety of Chronic Total Occlusion Percutaneous Coronary Intervention via Distal Transradial Access - Lin, Cheng-Jui; Lee, Wei-Chieh; Lee, Chieh-Ho; Chung, Wen-Jung; Hsueh, Shu-Kai; Chen, Chien-Jen; Yang, Cheng-Hsu; Fang, Hsiu-Yu; Cheng, Cheng-I; Wu, Chiung-Jen (Frontiers in Cardiovascular Medicine, 2021)
Aims The current study aims to verify the feasibility and safety of chronic total occlusion (CTO)-percutaneous coronary intervention (PCI) via the distal transradial access (dTRA). Methods Between April 2017 and December 2019, 298 patients who underwent CTO PCI via dTRA were enrolled in this study. The baseline demographic and procedural characteristics were listed and compared between groups. The incidences of access-site vascular complications and procedural complications and mortality were recorded. Results The mean J-CTO (Japanese chronic total occlusion) score was 2.6 ± 0.9 points. The mean access time was 4.6 ± 2.9 min, and the mean procedure time was 115.9 ± 55.6 min. Left radial snuffbox access was performed successfully in 286 patients (96.5%), and right radial snuffbox access was performed successfully in 133 patients (97.7%). Bilateral radial snuffbox access was performed in 107 patients (35.9%). 400 dTRA (95.5%) received glidesheath for CTO intervention. Two patients (0.7%) developed severe access-site vascular complications. None of the patients experienced severe radial artery spasm and only 2 patients (0.5%) developed radial artery occlusion during the follow-up period. The overall procedural success rate was 93.5%. The procedural success rate was 96.5% in patients with antegrade approach and 87.7% in patients with retrograde approach. Conclusions It is both safe and feasible to use dTRA plus Glidesheath for complex CTO intervention. The incidences of procedure-related complications and severe access-site vascular complications, and distal radial artery occlusion were low.